Peran Investasi, Utang Luar Negeri, dan Inflasi Bagi Pertumbuhan Ekonomi Indonesia - Tubagus Thresna Irijanto; Dheany Mega Lestari (Jurnal Riset Ilmu Ekonomi, 2022)
This study aims to explain the influence of variable foreign debt, foreign investment, domestic investment and inflation on Indonesia's economic growth. Researchers observed research variables in the period 1994-2018 with variables of economic growth as dependent variables. In this study, researchers used cross-section data processed by the Error Correction Model (ECM) method. Based on the results of the ECM method, research researchers can explain the influence of variables on a holistic scale in the long and short term. The results of the study explain that in the long run, economic growth can be positively affected by foreign debt significantly. But on the other hand, in the short term, the results of research show that domestic investment and foreign debt both have a significant positive influence on economic growth. From these results, there are differences in the influence of independent variables in each time period. Although there are differences in the influence of independent variables on each time period, but researchers concluded that from the results of processing data variables foreign debt is equally a significant positive effect on national economic growth.